Optimization of a horizontal slot waveguide biosensor to detect DNA hybridization - Viphavakit, Charusluk; Komodromos, Michael; Themistos, Christos; Mohammed, Waleed S.; Kalli, Kyriacos; Rahman, B. M. Azizur (My University, 2015)
A full-vectorial H-field formulation-based finite element approach is used to optimize a biosensor structure incorporating a horizontal slot waveguide. It is designed to detect DNA hybridization through the change of the effective index of the waveguide structure. The key parameters, such as normalized power confinement, power density, change in effective index, and sensitivity are presented by optimizing the device parameters of the slot waveguide. It is shown here that a 90.0 μm long compact Mach-Zehnder section can be designed with horizontal slot waveguide to detect DNA hybridization and for a ring resonator arrangement a sensitivity of 893.5 nm/RIU is obtained.
Keywords: DNA; DNA, Single-Stranded; Equipment design; Models theoretical; Oxides; Oxygen; Refractometry; Reproducibility of results; Silicon; Silicon dioxide; Biosensing techniques; Nucleic Acid Hybridization